Vinti's Surface Density as a Means of Representing the Earth's Disturbance Potential - Harijono Djojodihardjo (Institute for Research and Community Services (LPPM) ITB, 1974)
Abstract. Vinti's method of representing the potential of the earth in two parts, with the first part represented by spheroidal potential and the second part being the earth disturbance potential, is outlined. The earth's disturbance potential is then represented as a surface distribution Ïƒ of mass density of variable sign over a sphere S just clearing the earth. The feasibility of the method is evaluated by calculating the distribution of o from satellite determination of the harmonic coefficients. Ringkasan. Suatu metoda untuk menyatakan potensial bumi berdasarkan teori Vinti diuraikan. Menurut metoda ini, potensial bumi dinyatakan sebagai jumlah potensial utama, yang diperoleh sebagai potensial spheroid, dan potensial gangguan, yang dinyatakan sebagai distribusi kerapatan masa permukaan pada suatu bola yang tepat menyelubungi bumi. Kegunaan metoda ini diuji dengan menghitung distribusi Ïƒ dengan menggunakan koefisien-koefisien harmonik yang ditentukan dari analisa data satelit.